2021
DOI: 10.1055/s-0041-1735978
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia and Ischemic Stroke: A Potential Dose-Response Association—A Systematic Review and Meta-analysis

Abstract: Background and Purpose Previous studies suggest an association between increased homocysteine (Hcy) and risk of ischemic stroke. Yet, it remains unknown whether a dose-response association exists between Hcy levels and risk of ischemic stroke. Methods Systematic literature searches were performed in PubMed, Embase, Scopus, and Web of Science. Inclusion criteria were studies investigating ischemic stroke risk in an adult population with measured Hcy levels. We computed odds ratios (ORs) for a 5 µmol/L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 106 publications
(277 reference statements)
4
10
0
1
Order By: Relevance
“…58 Another meta-analysis showed a dose-response of the risk association of t-Hcy with ischemic stroke with a 43% increased risk per 5 µmol/L increase in t-Hcy level. 59 A third meta-analysis of 10 prospective studies found a pooled RR at 1.06 for stroke and 1.05 for ischemic stroke for each 1-µmol/L increase of t-Hcy. 60…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…58 Another meta-analysis showed a dose-response of the risk association of t-Hcy with ischemic stroke with a 43% increased risk per 5 µmol/L increase in t-Hcy level. 59 A third meta-analysis of 10 prospective studies found a pooled RR at 1.06 for stroke and 1.05 for ischemic stroke for each 1-µmol/L increase of t-Hcy. 60…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…58 Another meta-analysis showed a dose-response of the risk association of t-Hcy with ischemic stroke with a 43% increased risk per 5 µmol/L increase in t-Hcy level. 59 A third meta-analysis of 10 prospective studies found a pooled relative risk at 1.06 for stroke and 1.05 for ischemic stroke for each 1 µmol/L increase of t-Hcy. 60 Despite these multiple sources of evidence, it is noteworthy that a very limited interest was directed to patients with intermediate and major HHcy.…”
Section: Observational Evidence Of the Dose-effect Association Of Hom...mentioning
confidence: 99%
“…Elevated HCY could promote oxygen free radical generation and damage the vascular endothelium leading to platelet aggregation and thrombosis ( 37 ). Furthermore, a meta-analysis indicated that a non-linear association could exist between HCY levels and risk of IS ( 38 ). Therefore, we analyzed the correlation between HCY levels and CR, and confirmed that high HCY levels significantly correlated to CR (OR 1.209; 95% CI 1.072–1.362; p = 0.002), which was consistent with another study ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Гомоцистеин -интегративный показатель эндотелиальной дисфункции, доступный в рутинной клинической практике [26,27]. Ранее были опубликованы работы, указываю щие на вклад гипергомоцистеинемии в замедление вестибулярной реабилитации после перенесенного вестибулярного нейронита [28], а также ухудшение показателей постуральной устойчивости [29].…”
Section: гомоцистеинunclassified